How the Fed reanimated Wall Street: The low and extended lending rates that revived the big banks - Nicola Matthews (Levy Economics Institute of Bard College, 2013)
Walter Bagehot's putative principles of lending in liquidity crises - to lend freely to solvent banks with good collateral but at penalty rates - have served as a theoretical basis for thinking about the lender of last resort for close to 100 years, while simultaneously providing justification for central bank real-world intervention. If we presume Bagehot's principles to be both sound and adhered to by central bankers, we would expect to find the lending by the Fed during the global financial crisis in line with such policies. Taking Bagehot's principles at face value, this paper aims to examine one of these principles - central bank lending at penalty rates - and to determine whether it did in fact conform to this standard. A comprehensive analysis of these rates has revealed that the Fed did not, in actuality, follow Bagehot's classical doctrine. Consequently, the intervention not only generated moral hazard but also set the stage for another crisis. This working paper is part of the Ford Foundation project A Research and Policy Dialogue Project on Improving Governance of the Government Safety Net in Financial Crisis and continues the investigation of the Fed's bailout of the financial system - the most comprehensive study of the raw data to date.
Keywords: E4; E5; G1; 330; lender of last resort; global financial crisis; monetary policy; Fed lending rates; Bagehot's classical doctrine; Fed emergency credit and liquidity facilities